Pulmonary Hamatroma - Pandey, Greta; Thakur, Binay (Nepalese Journal of Cancer, 2021)
Pulmonary hamartoma are common benign tumor of lung. These are composed of variable components of cartilage, fat, smooth muscles and respiratory epithelium. Most patients are asymptomatic with few present with pulmonary symptoms. The neoplasm is less common in young with surgical excision being the treatment of choice. Histopathology revealed the true pathological nature of the tumor.